PDGFRA mRNA overexpression is associated with regional metastasis and reduced survival in oral squamous cell carcinoma. (27th June 2018) - Ong, Hui Shan; Gokavarapu, Sandhya; Tian, Zhen; Li, Jiang; Xu, Qin; Zhang, Chen Ping; Cao, Wei
Abstract : Background: Platelet‐derived growth factor alpha (PDGFRA) is a gene encoding tyrosine kinase receptor and both EGFR and PDGFRA activate tyrosine kinases. The implication of PGFRA in many cancers and its prognostic significance irrespective to EGFR status in spinal chordoma, gliomas, and uterine cancers have shown a need for its investigation in oral squamous cell carcinoma (OSCC). We investigated the prognostic value of PDGFRA mRNA expression in OSCC. Patients and methods: The study was conducted in the department of oral maxillofacial surgery‐head and neck oncology, at a tertiary hospital. The data on PDGFRA mRNA expression and immunohistochemical staining status in primary OSCC patients treated for curative surgery from 2010 to 2012 were analyzed. Univariate and multivariate analyses were performed with other cofactors for survival. Results: A total of 114 consecutive patients with primary OSCC who received treatment were studied. Thirty‐one patients died of the disease. Strong PDGFRA immunohistochemical staining and high expression of PDGFRA mRNA were associated with positive pN status ( P  <   .001), disease‐free survival ( P  <   .001), and overall survival ( P  <   .001) in multivariate cox regression when all other factors such as pN status and histological grading were analyzed. Kaplan‐Meier analysis revealed that the 2‐year survival and 3‐year survival of patients with PDGFRA mRNA low expression were 96.83%. However, 2‐year survival for PDGFRA mRNA high expression level was 59.64%, which decreased to 45.57% by 3‐years. Conclusion: PDGFRA overexpression in oral SCC, in respect to strong PDGFRA immunohistochemical staining and high PDGFRA mRNA expression, was positively associated with regional metastasis and reduced patient survival.